To solve \(-123.45 - (-234.76)\), we can use the additive inverse property, which states that subtracting a negative number is the same as adding its positive counterpart.
So, we rewrite the expression:
\[ -123.45 - (-234.76) = -123.45 + 234.76 \]
Now we perform the addition:
- First, let's find the difference between the two numbers: \[ 234.76 - 123.45 \]
We can align these numbers for clarity:
234.76
- 123.45
__________
- Now we subtract:
- Start from the rightmost column: 6 - 5 = 1
- Next column: 7 - 4 = 3
- Next column: 4 - 3 = 1
- Finally, 2 - 1 = 1
So:
\[ 234.76 - 123.45 = 111.31 \]
Thus:
\[ -123.45 + 234.76 = 111.31 \]
The final answer is:
111.31